Masculinities and hydropower in India: a feminist political ecology perspective - Shrestha, Gitta; Joshi, Deepa; Clement, Floriane (Uopen Journals, 2019)
Mainstreaming gender in water governance through “how to do gender” toolkits has long been a development focus. It has been widely argued that such toolkits simplify the complex, nuanced realities of inequalities by gender in relation to water and fail to pay attention to the fact that the proposed users of such gender-water toolkits, i.e. mostly male water sector professionals, lack the skills, motivation and/or incentives to apply these toolkits in their everyday work. We adopt a feminist political ecology lens to analyse some of the barriers to reduce social inequalities in the management of global commons such as international rivers. Our findings highlight the leap of faith made in the belief that gender toolkits, as they exist, will filter through layers of a predominantly masculine institutional culture to enable change in ground realities of complex inequalities by gender. Analysing the everyday workings of two hydropower development organisations in India, we show how organisational structures demonstrate a blatant culture of masculinity. These two organisations, like many others, are sites where hierarchies and inequalities based on gender are produced, performed and reproduced. This performance of masculinity promotes and rewards a culture of technical pride in re-shaping nature, abiding by and maintaining hierarchy and demonstrating physical strength and emotional hardiness. In such a setting, paying attention to vulnerabilities, inequalities and disparities are incompatible objectives.